Assessing spatial and temporal variation in obligate resprouting, obligate seeding, and facultative seeding shrub species in California’s Mediterranean-type climate region - Underwood, Emma C.; Sorenson, Quinn M.; Schrader-Patton, Charlie C.; Molinari, Nicole A.; Safford, Hugh D. (Frontiers in Ecology and Evolution, 2023)
Mediterranean-climate region (MCR) shrublands have evolved a set of regeneration strategies in response to periodic, high intensity wildfires: obligate seeding (OS), obligate resprouting (OR), and facultative seeding (FS) species. In the North American MCR, data on their spatial and temporal variability is currently lacking, which is a significant information gap for resource managers. We developed a multinomial model using dynamic and static variables to predict the distribution of the three shrub post-fire regeneration strategies, plus trees and herbs, in southern California. Cross-validation showed 50% of the predicted values for each of the five plant groups were within 8-24 percent of the actual value. We assessed variation in shrub regeneration strategies in three ways. First, we found the three major shrub community types (mixed chaparral, chamise-redshank chaparral, and coastal sage scrub) had proportionally greater biomass of FS (37-43% of total biomass) than OR or OS. Second, we assessed the spatial variability using (a) moisture availability (climatic water deficit and solar radiation) and found FS accounted for an increasingly greater proportion of total aboveground live biomass as water became limited, while OR biomass decreased; and (b) ecosystem productivity (NDVI) which showed the proportion of OS, OR, and tree biomass increased with productivity (with a corresponding dramatic decrease in herb biomass). We also assessed temporal variability using time since fire and found OS represented an initially small proportion of total biomass immediately post-fire (8–10%) which increased with time since fire (13–17%). Third, spatial outputs from the multinomial model indicated FS dominated pixels were most widely distributed across the study area (~3.4 million ha, 71%), compared to OR and OS covering 5% each. FS also occurred more frequently on warmer, south facing slopes and summits whereas OR preferred cooler, north facing slopes and valleys (p < 0.0001). Better understanding the distribution of OS, OR, and FS shrubs is important for resource management, including quantifying shrubland carbon storage and identifying areas for post-fire restoration, as described in a case study of the Bobcat Fire on the Angeles National Forest.